Perencanaan Rumah Dua Lantai Dengan Struktur Beton Bertulang Dan Rangka Atap Baja Ringan Prefabrikasi Di Daerah Rawan Gempa: Structural Design Of Two Story Reinnforced Concrete Residential House With Prefabricated Light Steel Roof Frame In Earthquake Areas - Fitria, Winda; Guspari, Oni; Putra, Roni Tri; Arazka, Wahyu; Effendi, Effendi; Afriyani, Sicilia; Gusnita, Riza (Media Ilmiah Teknik Sipil, 2025)
This study aims to design a two-story earthquake-resistant house in Padang City with reinforced concrete structural system for columns, beams and foundations, combined with prefabricated lightweight steel roof frame. The design procedure refers to SNI 1727 2020 for minimum loads, SNI 2847 2019 on requirements for reinforced concrete and SNI 1726 2020 on seismic design procedures for buildings. 3D model was developed using sap2000 application to obtain internal forces and support reactions of the building. The foundation design was analyzed by Terzhagi’s method with consideration of the local soil conditions. The result indicate that the designed structural elements meet the strength requirements for earthquake resistant house in Padang. The use of prefabricated light steel roof frame does not significantly affect the total structural weight, but contributes to time efficiency during construction. The structural DED produced in this study is expected to serve as a practical reference for earthquake- resistant housing development in Padang. This research highlights the importance of applying seismic standards even to residential buildings.